The Interpersonal Needs Questionnaire: Statistical Considerations for Improved Clinical Application. (April 2020) - Mitchell, Sean M.; Brown, Sarah L.; Roush, Jared F.; Tucker, Raymond P.; Cukrowicz, Kelly C.; Joiner, Thomas E.
The interpersonal theory of suicide (ITS) has accumulated empirical support; however, less research has investigated the clinical utility of ITS constructs in suicide risk assessment. The current study sought to increase the clinical utility of the Interpersonal Needs Questionnaire (INQ), an assessment of thwarted belongingness (TB) and perceived burdensomeness (PB), among 318 adult psychiatric outpatients while considering statistical methodology (i.e., multicollinearity and partialling). Results emphasized PB in the prediction of concurrent desire for death/suicide when TB was simultaneously considered. The interaction between TB and PB did not enhance prediction of concurrent desire for death/suicide. Independently, PB was a stronger predictor than TB of concurrent desire for death/suicide in the total sample and gender subsamples. Estimated probabilities of concurrent desire for death/suicide across INQ scores and preliminary INQ clinical cutoff scores are provided to enhance clinical application. These findings suggest the INQ could provide valuable information for suicide risk assessment and conceptualization.